O processo de aprendizagem do cozinhar em João Pessoa/PB à luz das práticas sociais e da estética organizacional - Soares, Lídia Cunha (2015)
The goal of this study was to analyze the learning process of cooking on the taste formation of two restaurants of regional food in Joao Pessoa in the light of the social practices and of the organizational aesthetics. The organizational aesthetics (STRATI, 1992, 2007a; 2007b; 2010; 2014) is the capability we have to activate the touch, the smell, the gustatory, the vision, the hearing and the aesthetics judgment while we live the experience. Through the aesthetics it is possible to access the sensitive knowledge, which is tacit and practical. The social practices correspond to the modes of doing and reproducing of a society and are formed by a set of activities the repeats over time. As a practice is done immediately it is learned, but it is learned in a social way, contextual and procedural as getting involved with the practice the social legitimation happens. The social learning through the situated perspective, the social practices, the organizational aesthetics and the sensitive knowledge made possible the study of the gastronomy, this one is formed by various practices: the food culture, the eating and the cooking. All of these aspects are surrounded by distinct service. The dimension of gastronomy that emerged in the market as most significant on the taste formation was the cooking. This way, it was conducted a study of ethnographic inspiration with aesthetic style (STRATI, 2007a) done in two restaurants specialized in regional cuisine in the city of Joao Pessoa. The empirical material collection was operationalized by participant observations, informal conversations, semi structured interviews and the pictures from the kitchens of the restaurants. Directed by the the zooming in and zooming out strategy (NICOLINI, 2009), done by guiding questions . The immersion on the field happened along seven months, being, on RI from the 9 th of June of 2014 until the 11th of January of 2015, and on the RII from the 27th of June of 2014 until the 14th of January in 2015. With forty-six visits total, being twenty on the RI and sixteen on the RII, with a hundred seven field hours total. The empirical material analysis was done by the imaginary participative observation and interpretative evocative analysis. Throughout the process the empirical material was analyzed separately, and the first composition of aesthetic text of ethnographic inspiration, took place in September of 2014, what made possible the identification of cooking as a practice. The results indicate that the studied restaurants are predominantly picturesque on their decoration evocating elements related to the regional food that were symbolically planned to provoke a sensorial-aesthetic experience; the learning of cooking happens though a peripheral legitimation process, where the cooks use their perceptive faculties and the collective aesthetic judgment to learn to cook. It was identified the importance of the aesthetic perception of the hands, the ears, the gustatory sense, the nose, the eyes and the aesthetic judgment on the reproduction of cooking as a practice with a regional focus; The locus of knowledge on cooking as a practice is the physical body, and the learning, the generation and the transmission of knowledge of cooking on the formation of taste happens in the physical body where it is possible to live an aesthetic experience reaching the sensitive knowledge. Stands out, yet, the gustatory faculty and the social construction and historical (regional) as fundamental to the development of taste; The immersion of the researcher in the field made possible the perception of a series of aesthetic categories while the cooking as a practice was developed, the picturesque, the agogic categories, the beauty and the ugliness. Finally, it was concluded that the cooking on the taste formation is learned through the sensitive knowledge, the tangible, the visual, the hearing, the olfactory, the gustative and the aesthetic judgment that is expressed by the social construction and regional collectiveness.